Understanding the aetiology and resolution of chronic otitis media from animal and human studies - Mahmood F. Bhutta; Ruth B. Thornton; Lea-Ann S. Kirkham; Joseph E. Kerschner; Michael T. Cheeseman (The Company of Biologists, 2017)
Inflammation of the middle ear, known clinically as chronic otitis media, presents in different forms, such as chronic otitis media with effusion (COME; glue ear) and chronic suppurative otitis media (CSOM). These are highly prevalent diseases, especially in childhood, and lead to significant morbidity worldwide. However, much remains unclear about this disease, including its aetiology, initiation and perpetuation, and the relative roles of mucosal and leukocyte biology, pathogens, and Eustachian tube function. Chronic otitis media is commonly modelled in mice but most existing models only partially mimic human disease and many are syndromic. Nevertheless, these models have provided insights into potential disease mechanisms, and have implicated altered immune signalling, mucociliary function and Eustachian tube function as potential predisposing mechanisms. Clinical studies of chronic otitis media have yet to implicate a particular molecular pathway or mechanism, and current human genetic studies are underpowered. We also do not fully understand how existing interventions, such as tympanic membrane repair, work, nor how chronic otitis media spontaneously resolves. This Clinical Puzzle article describes our current knowledge of chronic otitis media and the existing research models for this condition. It also identifies unanswered questions about its pathogenesis and treatment, with the goal of advancing our understanding of this disease to aid the development of novel therapeutic interventions.